EFEKTIFITAS POSISI TIDUR SEMI FOWLER DENGAN KUALITAS TIDUR PADA PASIEN ASMA DI RUANG RAWAT INAP PERAWATAN PARU RSUD BANGKINANG TAHUN 2017 - Nila Kusumawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Sleep as one part of the physiological needs are basic needs that are needed by all humans. Someone came in and hospitalized, sleep patterns can be easily changed and impaired as a result of illness and hospital routine unknown. The purpose of this study aims to determine the effectiveness of bed semi-Fowler's position with the quality of sleep in patients with asthma in the hospital inpatient pulmonary disease Bangkinang. This study is an analytical type with Quasi Experiment design. The sampling technique using sampling purfosive as many as 20 people. Analysis of the data used are univariate (central tendency) and bivariate (t test dependent). The results showed that the mean difference in the quality of sleep in the two groups: (18.80 + 1.795: 2.798 + 15.40). Visible differences in mean values between the two groups was 3.40 with a standard deviation of 1.003, the differences were statistically significant (p <0.05). This means sleeping position semifowler effectively to improve the quality of sleep in patients with asthma in the lung space Bangkinang. Expected at the hospital to be able to apply the sleeping position is an appropriate solution in asthmatic patients with rest and sleep disorders.